Participation in Poverty Assessments - World Bank (Washington, DC, 2012)
The Bank ' s approach to country poverty assessments (PAs) is increasingly stressing the involvement of stakeholder groups, with the aim of building in-country capacity to address the problems of the poor. The participation of government and other institutional stakeholders in all aspects of the work increases sensitivity to poverty issues, enhances analytical skills, and builds allegiance to the measures proposed for poverty reduction. In addition, conventional statistical analysis is complemented by qualitative information from participatory social assessments, known as " PPAs, " which reveal the concerns voiced by the poor. Some early lessons for task managers have already emerged from this experience.